The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1081/wct-120016260
|View full text |Cite
|
Sign up to set email alerts
|

Pulping and Bleaching of Partially Cad-Deficient Wood

Abstract: Mutant loblolly pine trees that are partially deficient in cinnamyl alcohol dehydrogenase (CAD) have been studied as a possible new source of pulpwood. Young (4-and 6-year-old) partially CAD-deficient pine trees are -20% more easily delignified (pulping and bleaching) and provide similar pulp yields to that of similarly aged normal pines grown on the same plots. Bleached pulp from a 6year-old partially CAD-deficient pine tree displayed better strength properties than the same age normal pine tree; this probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In addition to lignin composition changes, the cad‐n1 allele appears to be associated with increased stem‐growth traits in heterozygous trees (Wu et al ., 1999). This growth promotion correlates to an increase in the debarked volume of 4‐year‐old trees (14%) (Wu et al ., 1999) that is also observed in 14‐year‐old trees (Dimmel et al ., 2002). A possible explanation could be that trees harbouring the cad‐n1 allele may invest fewer resources into the production of monolignols, allowing reallocation of resources towards growth.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition to lignin composition changes, the cad‐n1 allele appears to be associated with increased stem‐growth traits in heterozygous trees (Wu et al ., 1999). This growth promotion correlates to an increase in the debarked volume of 4‐year‐old trees (14%) (Wu et al ., 1999) that is also observed in 14‐year‐old trees (Dimmel et al ., 2002). A possible explanation could be that trees harbouring the cad‐n1 allele may invest fewer resources into the production of monolignols, allowing reallocation of resources towards growth.…”
Section: Introductionsupporting
confidence: 54%
“…In totally CAD‐deficient trees ( cad‐n1/cad‐n1 ), delignification was significantly easier but the pulp yields were relatively low (∼33%) compared to normal trees (48%) (Dimmel et al ., 2001). In 4–6‐year‐old partially CAD‐deficient trees (heterozygous) delignification increased in efficiency by ∼20% and yields were similar to the wild‐type (Dimmel et al ., 2002). In contrast to these younger trees, a small sample of 14‐year‐old partially CAD‐deficient trees displayed no major differences in ease of delignification and pulp yield (Dimmel et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more suitable native lignin may allow for a reduced alkali charge, lower cooking temperature, and/or decreased retention time. As these conditions result in milder cooking conditions, an increase in pulp yield and fiber quality may be expected (Dimmel et al 2001(Dimmel et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significantly less energy was required (15 to 25% lower H-factor) to pulp to a given kappa number than for wild-type trees and the pulp of the heterozygotes was brighter and stronger [2]. On the contrary, Dimmel et al [3] found no apparent differences in ease of delignification or pulp yield between heterozygous and wild-type trees that were 14 years old. In a much larger sample, effects associated with this cad-n1 allele were found by comparing wood density and growth traits of cad-n1 heterozygous trees with wild-type trees in a 10-year-old open-pollinated family experimentally growing under two levels of fertilization.…”
Section: Introductionmentioning
confidence: 94%